Experience and local memory of older people in the face of disasters: a systematic review - Navarrete-Valladares, Camila; Sandoval-Díaz, José; Sandoval-Obando, Eduardo (Frontiers in Public Health, 2023)
Introduction The increase in population aging establishes new risk scenarios in the face of the intensification of disasters due to climate change; however, previous experiences and collective memory would generate opportunities for older people to acquire adaptive and coping capacities in the face of these events. Objective To analyze the theoretical-methodological characteristics presented by the studies carried out between the years 2012 and 2022 about the experience and collective memory of the older adult in the face of climate change. Method A systematic literature review (SLR) was carried out following the guidelines of the PRISMA statement. The databases consulted were Web of Science, Scopus, EBSCO host, and Redalyc, selecting 40 articles in Spanish, English, and Portuguese. Results The importance of experience and collective memory in the face of disasters as an adaptive factor in older people was identified. In addition, sharing experiences allows them to give new meaning to what happened, emphasizing confidence in their personal resources and self-management capacity and fostering perceived empowerment. Discussion It is essential that in future studies the knowledge provided by the older adult can be privileged, recognizing the importance of their life histories and favoring the active role in their development and wellbeing.